In Operando Visualization of SOFC Electrodes by Thermography and Visible Light Imaging. (1st January 2015) - Tachikawa, Y.; Sugimoto, J.; Takada, M.; Kawabata, T.; Lyth, S. M.; Shiratori, Y.; Sasaki, K.
Abstract : The temperature distribution in internal reforming SOFC anodes can be visualized by thermography. However, thermal imaging techniques are limited since they cannot take into account the influence of emissivity changes caused by carbon deposition on the anode. This problem can be solved by simultaneous visualization using thermography and visible light imaging. By combining these techniques, carbon deposition can be monitored via visible light imaging, whilst temperature changes due to the reforming reaction can be monitored by thermal imaging. This in operando visualization technique enables the evaluation and prediction of the distribution of multiple chemical reactions on the SOFC electrodes.